Le régime du caoutchouc : esclavage et travail forcé. Le Congo de Léopold II, 1885-1908 - Loffman, Reuben (Les mondes de l'esclavage: une histoire comparée, 2021)
Keywords: Tippo Tip (1837-1905)

God's Laborers: Missionary Work and Imperialism in the Congo From 1878-1908 - Peterson, Ana (Utah State university, 2024)
In 1878, Henry Craven opened the first Protestant mission in the Congo. The Livingstone Inland Mission created multiple stations along the Congo River to reach the interior. It stayed active for six years before transferring its stations to Swedish and American missions. Five years after its closure, a sister mission, the Congo Balolo Mission, resumed efforts to teach the people living in the interior. This thesis explores the evolving reaction of the missionaries to state violence. It argues that these missionaries initially supported imperial violence that enforced laws that aligned with their beliefs, such as removing the slave trade. Once that violence extended to profits alone and increased in violence, the missionaries joined the movement to improve conditions in the Congo.
Keywords: Esclavage -- Zanzibar; Tippo Tip (1837-1905)

An Abolitionist Vicious Circle: Slaving, Antislavery, and Violence on the Shores of Lake Tanganyika at the Onset of Colonial Occupation - Rossi, Benedetta (Slavery & Abolition, 2024)
In the late nineteenth century, abolitionists felt entitled to use all possible means to save the African victims of the slave trade. As European imperialism rose, abolitionism legitimized interventionism. This article explores how a major humanitarian movement could sanction colonial occupation and the violence that accompanied it. It also examines the position of African slaveholders who resisted the entrenchment of European rule and defended an order in which slavery was common. It focuses on two main actors: French Captain Leopold Joubert, Catholic royalist and former pontifical Zouave who supported Cardinal Lavigerie's Missionaries of Africa and Belgian King Leopold II's allegedly abolitionist endeavours; and Tippu Tip, a trader and slaver who, like Joubert, worked for self-styled abolitionists such as Leopold II and the Sultan of Zanzibar. The connected microhistories of these men show how the international problematization of African slavery fuelled both European imperialism and anti-colonial resistance, while also creating circumstances in which enslaved persons emancipated themselves. The article investigates the moral perceptions of individuals whose sense of self was predicated upon values embodied by Europe's monarchies, the papacy of Rome, and the sultanate of Zanzibar. Faced with what they perceived as existential threats to these institutions, they responded with rising radicalism.
Keywords: Esclavage -- Zanzibar; Tippo Tip (1837-1905)

مغامر عماني في أدغال إفريقيا: حمد بن محمد بن جمعة المرجبي المعروف بتيبو تيب : سيرة ذاتية - المرجبي, محمد بن جمعة (منشورات الجمل, 2006)
Keywords: Tippo Tip (1837-1905)

Notices relatives à l'État indépendant du Congo et projets antérieurs ([1876-1884] 1885-1908) - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Belgique, Congo, Rwanda et Burundi : Guide des sources de l'histoire de la colonisation (19e-20e siècle), 2021)
Keywords: Archives -- Bruxelles; Esclavage -- Oman; Esclavage -- Zanzibar; Relations -- Oman -- Belgique; Tippo Tip (1837-1905)

Notices relatives à la Belgique et aux territoires sous autorité belge : Congo, Ruanda Et Urundi ([1884]1909-1960/1962) - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Belgique, Congo, Rwanda et Burundi : Guide des sources de l'histoire de la colonisation (19e-20e siècle), 2021)
Keywords: Archives -- Bruxelles; Esclavage -- Oman; Esclavage -- Zanzibar; Relations -- Oman -- Belgique; Tippo Tip (1837-1905)

Notices relatives aux territoires africains sous autorité allemande : Afrique Orientale Allemande (1890-1916) / Notices relatives aux archives d'origine allemande produites dans le cadre de l'occupation de la Belgique durant la Deuxième Guerre mondiale et concernant des sociétés belges actives au Congo et au Ruanda-Urundi - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Belgique, Congo, Rwanda et Burundi : Guide des sources de l'histoire de la colonisation (19e-20e siècle), 2021)
Keywords: Archives -- Bruxelles; Esclavage -- Oman; Relations -- Oman -- Belgique; Tippo Tip (1837-1905)

حمد تيبو تيب ودوره السياسي في وسط أفريقيا - طنش, أحمد محمد (مجلة القادسية في الاداب والعلوم التربوية, 2008)
Keywords: Tippo Tip (1837-1905)

Review : Muhammad al-Mahruqi (ed.), Mugamir 'umani fi adgal Ifriqya. Hayat Hamad bin Muhammad bin Jum'a Al-Murjabi (1840-1905), al-ma'riif bi-TibuTib [Un aventurier Omanais au coeur de l'Afrique. La vie de Hamad bin Muhammad bin Jum'a Al-Murjabi (1840-1900), connu sous le nom de Tippo Tip], Cologne, Al-Kamel, 2006 (210 p.). - Luffin, Xavier (Annales Aequatoria, 2008)
Keywords: Recension; Tippo Tip (1837-1905)

The ‘Autobiography’ of Tippu Tip: Geography, Genre and the African Indian Ocean - Decker, Michelle (Interventions, 2015)
Keywords: Tippo Tip (1837-1905); Zanzibar

ʿUmānī fī ‘l-Sharq al-Ifrīqī: ‟Tībū Tībˮ Nāẓiran wa-Manẓūran ilayhi - Saʿīdī, Aḥmad al- (al-Mu’tamar al-Duwalī : al-Dawr al-ʿUmānī fī ‘l-Sharq al-Ifrīqī, 11-13 Dec. 2012. Buḥūth al-Mu’tamar, 2014)
Keywords: Tippo Tip (1837-1905)

Tippu Tip: the story of his career in Zanzibar & Central Africa - Brode, Heinrich (Gallery Publications, 2000)
Keywords: Tippo Tip (1837-1905); Zanzibar

Stuart Laing. Tippu Tip: Ivory, Slavery and Discovery in the Scramble for Africa - Kyle, Michael (Asian Affairs, 2018)
Keywords: Esclavage -- Zanzibar; Recension; Tippo Tip (1837-1905)

The Life of Tippu Tip. Tippu Tip: Ivory, Slavery, and Discovery in the Scramble for Africa - Mathews, Nathaniel (The Journal of African History, 2019)
Keywords: Esclavage -- Zanzibar; Recension; Tippo Tip (1837-1905)

Tippu Tip: ivory, slavery and discovery in the scramble for Africa - Laing, Stuart (Medina Publishing Ltd, 2017)
Tippu Tip, notorious to some, intriguing to others, was a Zanzibari Arab trader living in the turbulent and rapidly changing Africa of the late 19th century. This biography transports the reader into his extraordinary world, describing its exotic cast of characters and the principal factors that shaped it. His colorful life culminated in his engagement as governor of a province in the 'Congo Free State' of the Belgian King Leopold, and in his involvement in Stanley's astonishing expedition to relieve Emin Pasha, governor of the Egyptian southern province of Equatoria. This book is the first thorough investigation in English of this significant figure. The lucid narrative unfolds against the political and economic backdrop of European and American commercial aims, while allowing the reader to see the period through African and Arab eyes. The fascinating figures who strutted the 19th-century African stage, and their hardly believable exploits, give this book an appeal reaching beyond the African specialist to the general reader
Keywords: Esclavage -- Zanzibar; Tippo Tip (1837-1905)